An ambient-temperature aqueous synthesis of zirconium-based metal–organic frameworks. Issue 23 (6th November 2018) - Pakamorė, Ignas; Rousseau, Jolanta; Rousseau, Cyril; Monflier, Eric; Szilágyi, Petra Ágota
Abstract : Illustration of the first ambient-temperature aqueous synthesis of the zirconium-based metal–organic framework NH2 -UiO-66. Abstract : For the first time, we have developed an aqueous ambient-temperature synthesis of the zirconium-based metal–organic framework NH2 -UiO-66. The optimised synthetic route offers greatly reduced energy input compared with the conventional solvothermal synthetic method and it does not require any organic solvents or vapours. This facile process is easily up-scalable and it yields highly porous nanoparticles. Samples that underwent the reaction in a shorter amount of time displayed point defects of the dangling linker type.